2019
DOI: 10.1002/pi.5878
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the chemistry of single‐ion conducting poly(ionic liquid)s with polyhedral boron anions

Abstract: The synthesis of a new family of single‐ion conducting random copolymers bearing polyhedral boron anions is reported. For this purpose two novel ionic monomers, namely [B12H11(OCH2CH2)2OC(O)C(CH3)CH2]2−[(C4H9)4N+]2 and [8‐(OCH2CH2)2OC(O)C(CH3)CH2‐3,3′‐Co(1,2‐C2B9H10)(1′,2′‐C2B9H11)]−K+, having methacrylate function, diethylene glycol bridge and closo‐dodecaborate or cobalt bis(1,2‐dicarbollide) anions were designed. Such monomers differ from previously reported ones by (i) chemically attached highly deloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 67 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…[1][2][3][4][5] Among the various derivatives of carboranes, special attention is paid to p-complexes of transition metals with carborane ligands, called metallacarboranes. The most known of them, cobalt bis(dicarbollide) [3,3 0 -Co(1,2-C 2 B 9 H 11 ) 2 ] À attracts increasing interest from researchers working in various elds from medical chemistry to [6][7][8][9][10][11] materials science [12][13][14][15][16][17][18] to due to its extraordinary high stability, low toxicity 19 and almost unlimited possibilities for chemical modication. 20,21 Recently, we suggested that cobalt bis(dicarbollide) can be used as a structural element in the design of molecular switches.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Among the various derivatives of carboranes, special attention is paid to p-complexes of transition metals with carborane ligands, called metallacarboranes. The most known of them, cobalt bis(dicarbollide) [3,3 0 -Co(1,2-C 2 B 9 H 11 ) 2 ] À attracts increasing interest from researchers working in various elds from medical chemistry to [6][7][8][9][10][11] materials science [12][13][14][15][16][17][18] to due to its extraordinary high stability, low toxicity 19 and almost unlimited possibilities for chemical modication. 20,21 Recently, we suggested that cobalt bis(dicarbollide) can be used as a structural element in the design of molecular switches.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated previously ,, that the highest ionic conductivity for linear methacrylate-based SICPs can be achieved by copolymerization of lithium ion containing monomers with PEGM. The presence of oxyethylene fragments in the side chain of poly­(PEGM), by analogy to PEO, significantly improves the solubility of ionic species, thus facilitating their dissociation and correspondingly enhancing the ionic conductivity of the resulting copolymers.…”
Section: Resultsmentioning
confidence: 91%
“…The investigation of block copolymer synthesis started with the RAFT polymerization of LiM monomer (LiMTFSI) using the poly­(TMC) precursor as the macro-RAFT transfer agent and AIBN as the initiator. DMF was chosen as a solvent due to its ability to dissolve both poly­(TMC) and LiM as well as because its utilization in (co)­polymerization of LiM monomer allowed for achieving high yields and high molecular weights of the resulting polyelectrolytes. ,, Using the optimal reaction conditions determined previously for RAFT polymerization of LiM ([AIBN]:[macro-RAFT] = 1:5 by mol, [DMF]:[poly­(TMC) + LiM] = 3:1 by weight), a set of poly­[TMC n - b -LiM m ] block copolymers (Table , copoly1–3) targeting different degrees of polymerization, were successfully prepared. The obtained ionic block copolymers were firm and densely packed yellowish rubber-like materials.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the attention on SICPEs is focused on ion pairing and cation–dipole interactions, which directly govern the dissociation and transport of Li + . Nevertheless, the interaction between anions and polymer matrices also correlates [ 66 ] with the movement ability and the ionic conductivity of SICPEs, mainly in two ways: [ 67 ] 1) The rigid groups in the polyanions, for example, phenyl groups in PSTFSI, would increase the T g of SICPEs. 2) Strong ionic crosslinking between the polyanion and polymer matrix through Li + hinders segmental mobility.…”
Section: Strategies To Increase the Ionic Conductivity Of Sicpesmentioning
confidence: 99%